RENAL ABSCESS IN SLE - A RARE PRESENTATION - NITHYALAKSHMI G,; BHARGAVI MV,; PALANIANDAVAN S, (International Journal of Pharma and Bio Sciences, 2016)
Systemic lupus erythematosis (SLE) is an autoimmune disorder. Abscesses involving various sites of the body have been reported in SLE. Renal abscess being very rare in SLE should be promptly diagnosed and treated to prevent sepsis and subsequent mortality. A 26 yr old lady with SLE presented with fever for 2 weeks and abdominal pain. She was found to have a large renal abscess due to MRSA (Methillin resistant Staphylococcus aureus). She recovered completely after antibiotic treatment and percutaneous drainage of the abscess. A definitive diagnosis of renal abscess due to MRSA is by microbiological culture of surgical specimen.